Awareness of HPV and HPV vaccine among college students in China - Li, Manman; Zhang, Fengzhi; Shi, Yun; Shi, Kaige; Li, Xiaoxue; Bai, Hua (Frontiers in Public Health, 2024)
Background Cervical cancer is the fourth most common cancer among women, HPV vaccine can reduce the incidence of cervical cancer by approximately 70%. Sexual behavior is a direct risk factor for HPV infection, and sexually active college students, therefore, receive attention for HPV vaccination. This study aimed to investigate the awareness of HPV and its vaccine among college students in Zhengzhou, and to explore the factors influencing their awareness of HPV vaccine, to understand college students’ willingness to receive the vaccine. The findings of this study will lay a foundation for cervical cancer prevention. Methods Using a multistage random sampling method, 650 college students from four universities in Zhengzhou were selected. A self-administered questionnaire on the awareness of HPV and its vaccine, and willingness to receive HPV vaccination was carried out. Logistic regression was used to analyze the factors influencing students’ awareness of the HPV vaccine. Results 58.0% of college students had heard of HPV, and 72.8% of college students had heard of HPV vaccine. Logistic regression showed that gender, major, grade, mean monthly consumption level, sexual history, and mother cervical cancer screening participation significantly influenced the awareness of HPV vaccine (p < 0.05). Only 27(4.2%) college students had received the HPV vaccine. 63.2% of college students expressed their willingness to get vaccinated. Conclusion The awareness of HPV and its vaccine among college students in Zhengzhou needs improvement. Although the vaccination rate is low, most college students are willing to be vaccinated. Diverse health education programs should be conducted for different groups to improve awareness of cervical cancer prevention and promote vaccination.